Shifting gender roles: an analysis of violence against women in post-conflict Uganda. Issue 3 (2nd April 2016) - Sengupta, Anasuya; Calo, Muriel
ABSTRACT: Based on findings from a qualitative study in northern Uganda, this article explores factors leading to gender-based violence (GBV) in the post-conflict African context. The crisis of masculinity becomes crucial to understanding women's vulnerability to GBV. This crisis stems from the trauma of losing one's internal resources – socially constructed identity role and purpose, and one's external resources – wealth and productive assets. We find that armed conflict replaces the positive male identity as household head with a destructive model of masculinity. It is the interaction between negative masculinities and extreme poverty that characterises the prevalence of GBV in such conditions.